Pengaruh Pengetahuan Pajak, Sosialisasi Pajak, dan Mutu Pelayanan Fiskus Atas Kepatuhan Wajib Pajak Serta Kesadaran Wajib Pajak Sebagai Variabel Intervening di 1 KPP Medan Kota - Nur Azizah (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2021)
The research wants to measure the influence of tax knowledge, tax socialization, and fiscus service quality for tax payers compliant such tax payers awarn to intervening variables in KPP Medan Kota. This research was take sample of 100 individual tax payers that registered in KPP Medan Kota. The data analysis use path analysis method. The r esearch result shows that tax knowledge, tax socialization, and fiscus service quality have significant result on tax payers awarn. Tax socialization and fiscus services quality have no significant result on tax payers compliant otherwise tax knowledge and tax payers awarn have significant result on tax payers compliant. So by Indirectly tax knowledge, tax socialization, and fiscus service quality have significant result on tax payers compliant to the tax payers awarn